Metabolic Syndrome-Related Kidney Injury: A Review and Update - Lin, Lirong; Tan, Wei; Pan, Xianfeng; Tian, En; Wu, Zhifeng; Yang, Jurong (Frontiers in Endocrinology, 2022)
Metabolic syndrome (MetS) includes visceral obesity, hyperglycemia, dyslipidemia, and hypertension. The prevalence of MetS is 20-25%, which is an important risk factor for chronic kidney disease (CKD). MetS causes effects on renal pathophysiology, including glomerular hyperfiltration, RAAS, microalbuminuria, profibrotic factors and podocyte injury. This review compares several criteria of MetS and analyzes their differences. MetS and the pathogenesis of CKD includes insulin resistance, obesity, dyslipidemia, inflammation, oxidative stress, and endothelial dysfunction. The intervention of MetS-related renal damage is the focus of this article and includes controlling body weight, hypertension, hyperglycemia, and hyperlipidemia, requiring all components to meet the criteria. In addition, interventions such as endoplasmic reticulum stress, oxidative stress, gut microbiota, body metabolism, appetite inhibition, podocyte apoptosis, and mesenchymal stem cells are reviewed.